Fragmented QRS Complex Has Poor Sensitivity in Detecting Myocardial Scar - Wang, Dee Dee (Ann Noninvasive Electrocardiol, 2010)
Objective: To study the association of the fragmented QRS complex versus the Q wave with myocardial scar and viability. Background: A prior study has suggested that the fragmented QRS complex on an electrocardiogram (ECG) is a highly sensitive and specific marker of myocardial scar as detected by regional perfusion abnormalities on a nuclear stress test. There is no external validation of this data. Methods: We correlated the ECG and nuclear perfusion images of 460 consecutive patients with known or suspected coronary artery disease. The presence of fragmented QRS or Q waves in two contiguous ECG leads was correlated with major coronary artery distributions on nuclear perfusion imaging. Results: For the 1842 evaluated territories, the fragmented QRS complex was not superior to the Q wave in detecting fixed or mixed myocardial defects. The fragmented QRS complex was associated with worse sensitivity (1.7%) in comparison to the Q wave (31.7%) for identifying myocardial scar. The fragmented QRS complex carried a higher false positive rate in patients with normal perfusion scans (15.8%, 221 segments), in comparison to Q waves (1.4%, 17 segments). Conclusion: In our study population, both the fragmented QRS and Q wave had poor sensitivity and specificity in detecting fixed or mixed myocardial scar. Larger studies are needed to evaluate fragmented QRS as a surrogate of myocardial scar before it can be incorporated into clinical practice. Ann Noninvasive Electrocardiol 2010;15(4):308‐314